2020
DOI: 10.1101/2020.05.07.082164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning with biomedical ontologies

Abstract: Ontologies have long been employed in the life sciences to formally represent and reason over domain knowledge, and they are employed in almost every major biological database. Recently, ontologies are increasingly being used to provide background knowledge in similarity-based analysis and machine learning models. The methods employed to combine ontologies and machine learning are still novel and actively being developed. We provide an overview over the methods that use ontologies to compute similarity and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Our previous work has also demonstrated that expansion of vocabulary [25] and ontology extension [26] can improve performance of a similar tasks. Recent work has also explored alternative methods for employing ontology axioms and taxonomy for classification and ranking problems, such as the conversion of ontology axioms to vectors [27], an approach which has been demonstrated to improve performance when compared semantic similarity approaches [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work has also demonstrated that expansion of vocabulary [25] and ontology extension [26] can improve performance of a similar tasks. Recent work has also explored alternative methods for employing ontology axioms and taxonomy for classification and ranking problems, such as the conversion of ontology axioms to vectors [27], an approach which has been demonstrated to improve performance when compared semantic similarity approaches [28].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work also showed that extension of ontologies by examining binary relations mined from text, and extension of ontology vocabularies with information from other ontologies, improved performance at a semantic similarity-based patient characterisation tasks [26, 27]. Recent work has also explored alternative methods for employing ontology axioms and taxonomy for classification and ranking problems, such as the conversion of ontology axioms to vectors [28], an approach which has been demonstrated to improve performance when compared semantic similarity approaches [29].…”
Section: Discussionmentioning
confidence: 99%
“…To provide DL2Vec with structured background knowledge of human and mouse phenotypes as well as protein functions, we used the crossspecies phenotype ontology PhenomeNET (Hoehndorf et al, 2011;Rodríguez-García et al, 2017), which is built upon and includes the Gene Ontology (Ashburner et al, 2000; The Gene Ontology Consortium, 2017). These ontologies contain formalized biological background knowledge (Hoehndorf et al, 2015b), which has the potential to significantly improve the performance of these features in machine learning and predictive analyses (Smaili et al, 2019;Kulmanov et al, 2020). DeepViral consists of a phenotype model trained on phenotypes caused by a viral infection and a sequence model trained on protein sequences, as shown in Figure 1 (b).…”
Section: Embedding Features Of Viruses and Human Proteins From Phenotmentioning
confidence: 99%
“…They also provide a rich semantic underpinning by means of description logics, enabling semantic information retrieval and analysis. Recent works in ontology-based machine learning and vectorisation, such as OPA2Vec [4], are bridging the gap between text mining, machine learning, and semantic analysis, and they highlight the need for novel approaches that make full use of the descriptive and semantic features provided by biomedical ontologies [5].…”
Section: Introductionmentioning
confidence: 99%